Removal of fluoroquinolone antibiotics by adsorption of dopamine-modified biochar aerogel - Bai, Hongjuan; Zhang, Qiaofei; Zhou, Xuan; Chen, Junhang; Chen, Zihan; Liu, Zhuangzhuang; Yan, Jun; Wang, Jing (The Korean journal of chemical engineering, 2023)
As emerging contaminants used for treating various tract infections, fluoroquinolones (such as enoxacin, ofloxacin, etc.) enter water bodies via point-source discharges of wastewater treatment plants and many of them raise environmental and health concerns. Herein, a novel adsorbent, derived from a useful renewable low-cost grapefruit peel, was prepared to investigate the adsorption behavior of fluoroquinolone antibiotics (enoxacin and ofloxacin). The obtained adsorbent was characterized by scanning electron microscopy (SEM), Fourier transform infrared (FTIR), X-ray diffraction (XRD) and thermo-gravimetric analysis and differential scanning calorimetry (TG-DSC). Further, the equilibrium sorption of the adsorption process was analyzed with isotherm models and kinetic models. Under optimal adsorption conditions, equilibrium data conformed to the Elovich model, and the kinetics of adsorption was fitted well with Redlich-Peterson model. Combined with thermodynamic analysis, electrostatic interaction, hydrogen bond, π-π stacking interaction were the possible adsorption mechanisms for both fluoroquinolone antibiotics onto the novel adsorbent. This work explored a promising adsorbent for the elimination of fluoroquinolone antibiotics in environmental remediation.